Tactics of treatment of patients with sexual dysfunctions and intermediate disorders - Кнігавко, Олександр Володимирович (Psychiatry, Neurology and Medical Psychology, 2019)
The article gives the world views on the main types of sexual disorders among the male contingent and their interrelation with the phases of sexual reaction. The interrelation of the development of sexual dysfunctions under the influence of significant stress or psychoemotional overload or in the absence of any psychoneurological disorders, among which the leading place occupy border disorder, is shown. The necessity of therapeutic correction of affective pathology in the complex therapy of sexual dysfunctions is substantiated. The basic mechanisms of complex treatment of sexual dysfunctions and psychopathological manifestations are shown. In order to work out a more effective therapeutic complex using the Questionnaire International Erectile Function Index (IEFI), calculation of the duration of sexual intercourse (the so-called Intravaginal latency interval (ILI) and the Hamilton Rating Scale for Depression (HDRS-17) were evaluated. 83 patients with sexual dysfunctions: 52 patients (1 group) with premature ejaculation (PE); 31 patients (2 groups) with erectile dysfunction (ED) (the presence of these sexual dysfunctions led to the development of anxiety-depressive and neurosis-like disorders, which was confirmed by the Hamilton Scales) and 45 patients (3 groups) with sexual dysfunctions that developed as a result of existing initial psychopathological or boundary disorders (BD). Each study group was divided into two subgroups (a and b), each of which used different therapies from each other. With the use of one or another therapeutic scheme, patients of each group received cognitive-behavioral psychotherapeutic correction, tadalafil, nootropic drugs (noofen or glycine) and antidepressants (fluoxetine or coaxiаl). The duration of the observation was 3 months. As a result of the study, improvement of the ejaculatory function (with an increase in the ILI score) was established, which significantly increased at each control examination. In the analysis of the dynamics of the overall indicator of the MIEF questionnaire after the therapy, improvement in sexual function was observed in all groups, but the best results were obtained in the ED group. The results of the HDRS questionnaire showed that after 3 months, patients in the PE group compared with the BD group were reliably less susceptible to depressive disorder, especially of a pronounced nature.